2022
DOI: 10.3390/nu14030713
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Whole-Grain Utilization in the Consumer Market: A Case Study of the Oldways Whole Grains Council’s Stamped Product Database

Abstract: Whole grains are a vital part of a healthy diet, yet there are insufficient data on the whole-grain content of commercial food products. The purpose of this research is to examine the long-term change in (1) measured whole grains in food products, (2) Whole Grain Stamp usage and (3) the prominence of whole-grain ingredients and product categories, across the United States and Latin America. These changes were quantified by analyzing the Oldways Whole Grains Council’s (WGC) Stamped Product Database from 2007 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Less than ideal average intakes per day were also present for other MSDP food groups, including whole grains, nonstarchy vegetables, fish, and olive oil. When juxtaposed against a 36% increase in whole grains in US food products since 2008 ( 47 ), whole grain intakes are low, especially among the nHA, with reported consumption of 0.65 oz eq per day (MSDP component score = 0.79 out of 10). The 75% of the study population making up the nHA achieved a total vegetable intake of ∼1 cup eq, which is lower than the 2–3 cups per day recommended by the DGA.…”
Section: Discussionmentioning
confidence: 99%
“…Less than ideal average intakes per day were also present for other MSDP food groups, including whole grains, nonstarchy vegetables, fish, and olive oil. When juxtaposed against a 36% increase in whole grains in US food products since 2008 ( 47 ), whole grain intakes are low, especially among the nHA, with reported consumption of 0.65 oz eq per day (MSDP component score = 0.79 out of 10). The 75% of the study population making up the nHA achieved a total vegetable intake of ∼1 cup eq, which is lower than the 2–3 cups per day recommended by the DGA.…”
Section: Discussionmentioning
confidence: 99%
“…A complementary approach is independent third-party certification of food products. A long-established example of this is the simple-to-understand Whole Grain Stamps of the Whole Grains Council [ 49 ]. There is some evidence that this latter approach can be useful in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that this latter approach can be useful in developing countries. In Latin America, the number of registered food products carrying the Whole Grains Stamp increased from approximately 100 when it was introduced in 2009 to more than 1300 in 2020 [ 49 ]. Further, a survey commissioned by the Whole Grains Council revealed that 2⁄3rds of consumers report that third-party labeling on foods gives them more confidence in the product, and more specifically that 86% of consumers trusted the Whole Grain Stamp [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we can observe an increasing demand for healthier food options. In both Latin America and the United States, a significant increase was recorded in the consumption of products containing whole grains (Sluyter et al, 2022). Bakery products are among the foods that are rich sources of fiber.…”
Section: Introductionmentioning
confidence: 99%